Simple Clinical Maneuver for Reducing Shoulder Pain Following Gynecologic Laparoscopic Surgery at Maharat Nakhonratchasima Hospital : A Randomized Controlled Trial - Chatchai Jantaweetip (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To assess the efficacy of simple clinical maneuver to reduce shoulder pain after gynecologic laparoscopic surgery.Study design: Randomized controlled trial.Materials and Methods: One hundred and four patients who were scheduled for elective gynecologic laparoscopic surgery were randomly allocated into 2 groups. Fifty-four patients in control group, CO2 was removed by passive deflation of the abdominal cavity through the cannula. Fifty patients in the intervention group, CO2 was removed using Trendelenbrerg position (30 degrees) and a pulmonary recruitment maneuver consisting of 5 manual lung inflations. Postoperative shoulder pain was recorded on a verbal rating scale (VRS 1-6) at 24 and 48 hours after the operation. Result: There was no significant difference in age, time of surgery, type of surgery, body mass index between 2 groups. Postoperative hospital stay (mean±SD) was 2.5 ± 0.57 days in the control group compared to 2.1 ± 0.47 days in the intervention group (p < 0.001). The significant pain is found in 11 in 50 patients (22%) in the intervention group compared with 34 in 54 patients (63%) in the control group (p < 0.001). More patients in the control group had significant pain compare to the intervention group (22% vs 63%, p < 0.001).Conclusion: This simple clinical maneuver significantly reduced shoulder pain after Gynecologic laparoscopic surgery.